2022
DOI: 10.1111/ijd.16255
|View full text |Cite
|
Sign up to set email alerts
|

Pyoderma gangrenosum following vaccination against coronavirus disease‐2019: a case report

Abstract: Pyoderma gangrenosum following vaccination against coronavirus disease-2019: a case report Dear Editor, Vaccination reduces the risk of infection and severity of coronavirus disease-2019 (COVID-19). However, various skin reactions associated with COVID-19 vaccination have been reported. 1 The most common skin adverse reactions are local site reaction, urticaria, morbilliform, and delayed large local reaction, while immune-mediated dermatoses and herpes virus reactivation are also observed. Here, we report a ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…There have been several studies reporting skin adverse events after COVID-19 vaccination, including PG [30][31][32][33][34]. This is not the case in our patient since her last COVID-19 vaccination was one year prior to her disease relapse.…”
Section: Discussionmentioning
confidence: 54%
“…There have been several studies reporting skin adverse events after COVID-19 vaccination, including PG [30][31][32][33][34]. This is not the case in our patient since her last COVID-19 vaccination was one year prior to her disease relapse.…”
Section: Discussionmentioning
confidence: 54%
“…A total of 164 non‐injection‐site reactions in 161 patients have been reported in previous case reports and series 7–88 . Patients with systemic lupus erythematosus (SLE) and lupus erythematosus profundus (LEP) showed exacerbation of lupus eruptions after 2 weeks, and other AEs developed several months later.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies over the past 2 years have reported skin side-effects after COVID-19 vaccination, including PG. 17 – 21 To the best of our knowledge, a PG ulcer triggered by COVID-19 vaccination in a patient with UC has not been reported.…”
Section: Discussionmentioning
confidence: 99%